Writing Techniques in Magical Realism Literary Works of S.E.A. Write Award Finalists, 1996 – 2021 - QI, ZHANG; Chaiprasert, Jansuda (Parichart Journal, 2024)
This article aimed to study writing techniques in magical realism literary works of the S.E.A. Write Award Finalists, during 1996 – 2021. Seven novels and thirty short stories were studied. The study found techniques of merging rational facts with magical surreal factors in literary elements of plot, characterization, and setting as the following. 1) Concerning plot, this included a mission leading to finding magical objects; characters encountering with magical phenomena, without clues or causes, accepted by people as normal public happenings; and telling of magical narratives, unproven and indistinct between reality and magic. 2) Regarding characterization, the realistic characters were presented as ordinary people in the society, and interacting with magical realistic characters, who were humans; animals; plants; things; or spirits in the real world with special characteristics or abilities. 3) Pertaining to setting, it was based on real locations added with magical events linking to historical period. Readers would assume the realistic magical events in historical timeline, uncertain whether the events happened or not. Besides, some magic was created on ancient beliefs, and this merged the realistic and the magical undividedly.